A study on the effect of PVDF on the structural and transport properties of polyaniline. Issue 4 (18th May 2020) - Jisha, P.; Suma, M. S.; Murugendrappa, M. V.; Raj, Kalyan
Abstract: The polymer composite of electrically conducting polyaniline with polyvinylidene fluoride is prepared to study the electrical conductivity and structural modifications. The electrical conductivity studies were made by varying frequency from 100 Hz to 5 MHz at room temperature. The AC conductivity remained almost constant at lower frequencies and for higher frequencies the conductivity increased. The PAni-PVDF composite exhibited better conductivity in comparison to the pure samples. The changes in dielectric properties against frequency variations were studied and exponential reduction in dielectric loss at very low frequencies was observed. The structural and morphological studies were carried out using XRD, FTIR, and SEM.